LA GESTION DE COMUNICACIÓN INTERNA EN EL DESARROLLO ORGANIZACIONAL EN EL CENTRO DE ESTUDIOS DE POSTGRADO Y EDUCACION CONTINUA DE LA UNIVERSIDAD TECNICA DE BABAHOYO. - VERONICA SUSANA DEFAZ MEDINA (2010)
INTERNAL COMMUNICATION MANAGEMENT IN ORGANIZATIONAL DEVELOPMENT IN THE CENTER FOR POSTGRADUATE STUDIES AND CONTINUING EDUCATION OF THE TECHNICAL UNIVERSITY OF BABAHOYO.